Policy brief on educationally-less-developed-states as a criterion for selecting undergraduate admission candidates into Nigerian federal universities (2025)
Interrogating data published by the Joint Admissions and Matriculation Board (JAMB) over the period 2017 to 2023 we present quantitative, verifiable and objective assessment of addressing the question of equity and justice in the adoption of Educationally-Less-Developed-States (ELDS) as a criterion for the selection of candidates for admission into undergraduate programmes in Nigerian Federal Universities. Some of the 23 states on the current list of ELDS, in particular Kwara and Kogi, have posted excellent results and are now in the First Quartile justifying that they ought to be taken off the list. The same applies to Nasarawa which is in the Second Quartile. On the other hand, Lagos and the Federal Capital Territory are in the Fourth Quartile and if the ELDS is to be retained both should be included in the list. The National Council on Education should take a closer look at this recommendation with a view to implementing same.